THE EFFECT OF THE SNOWBALL THROWING METHOD IN THE DISCOVERY LEARNING MODEL ON THE LEARNING OUTCOMES OF CLASS XI MIPA SMAN 22 MAKASSAR (MAIN STUDY OF BUFFER SOLUTION) - A. Fatimah Sahara; Army Auliah; Eda Lolo Allo (Universitas Negeri Makassar, 2024)
This research aims to determine the effect of the Snowball Throwing method in the Discovery Learning Model on the learning outcomes. This quasi-experimental research with a posttest-only control group design was carried out in the even semester of the 2023/2024 academic year. The research sample was determined at simple random from 6 classes of XI MIPA SMAN 22 Makassar as the research population. The research sample was class XI MIPA 3 as the experimental group and class XI MIPA 4 as the control group. Data collection was carried out by giving a multiple choices test at the end of the meeting. Based on results of data analysis using descriptive statistics, the average value for the experimental group was 80.16 and the control group was 68.66. Hypothesis testing with inferential statistical analysis using the Mann Whitney non-parametric test shows that the Zcount = 7.57 is greater than the Ztable = 1.64 at a significance level of 0.05. This shows that there is an influence of the Snowball Throwing method in the Discovery Learning Model on the learning outcomes of class XI MIPA students at SMAN 22 Makassar Basic Study of Buffer Solutions